ETHICAL COMMITTEE FOR RESEARCH OF THE INSTITUTE OF ONCOLOGY AND RADIOBIOLOGY - ORTIZ-REYES, Rosa María; ARBESÚ-MICHELENA, María Antonieta; VÁZQUEZ GONZÁLEZ, José Manuel (MEDECINE LEGALE DROIT MEDICAL, 2025)
Introduction: In 1995 was created the Ethical Committee for Research and the Institute of Oncology and Radiobiology (INOR) in the context of the development of the biotechnology industry. The aim of this article is to present the development of this Committee. Methods: This research is based on the review of archives of the direction, the department of clinical trials and of the Ethics Committee at INOR; Cuba’s norms of Good Clinical Practices were also examined as well as the archives from the Health Ministry, the Centre for the Coordination of Clinical Trials and the Cuban Regulatory Agency. Results: Nine restructurations were undertaken in order to cumply with both national and international norms. The Guide of Organization and Proceeding conceived was modified five times; the mean of clinical trials per year is 12, with a mean of response of 36,8 days and a level of approval and approval under modifications of 90,7%. The Committee undertak various scientific scientific and teaching activities, follow-up of clinical trials and evaluation of other types of research (biological sampling, studies on animals, studies, and research projects of other institutions). In November 2016 INOR was granted the certificate of GCP. Conclusion: INOR’s Etical Committee, pioneer in the country, has developped various activities, faced challenges, and provided solutions.